1987
DOI: 10.1055/s-2008-1025681
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Antihypertensive Therapy with Beta-Blockers: Submaximal Exercise Capacity and Metabolic Effects During Exercise

Abstract: The effects of long-term (6 months) antihypertensive treatment with three different types of beta-blockers (propranolol, nonselective without ISA; pindolol, nonselective with ISA; metoprolol, beta 1-selective without ISA) on submaximal exercise capacity and metabolic variables during submaximal endurance exercise were studied in seven subjects with essential hypertension. Exercise tests were performed on a bicycle ergometer at 70% of estimated VO2 max. Similar reductions of resting and exercise blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 19 publications
2
16
1
Order By: Relevance
“…We cannot be sure that our results are also valid for patients with higher levels of blood pressure. Although in most studies, treatment periods were longer than in our study, we do not consider this a very likely explanation for the discrepancies, since in normotensive subjects it has been shown that there is no difference in effect between a single dose and a chronic (Smyth et al, 1984;Van Baak et al, 1985). Based on the results obtained we have to reject the hypothesis that the effect of 1-adrenoceptor blocker administration on exercise haemodynamics differs between normotensive and hypertensive subjects.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…We cannot be sure that our results are also valid for patients with higher levels of blood pressure. Although in most studies, treatment periods were longer than in our study, we do not consider this a very likely explanation for the discrepancies, since in normotensive subjects it has been shown that there is no difference in effect between a single dose and a chronic (Smyth et al, 1984;Van Baak et al, 1985). Based on the results obtained we have to reject the hypothesis that the effect of 1-adrenoceptor blocker administration on exercise haemodynamics differs between normotensive and hypertensive subjects.…”
Section: Discussioncontrasting
confidence: 63%
“…In this study, we confirmed the finding of previous studies (Anderson etal., 1979;Folgering & Van Bussel, 1980;Hughson & MacFarlane, 1981;Tesch & Kaiser, 1983;Smyth et al, 1984;Van Baak et al, 1985 , 1982Lijnen etal., 1979;Leenen et al, 1980;Losment et al, 1986). One possible explanation for the discrepant findings is that most of the studies mentioned above may have suffered from methodological bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have shown that total energy expenditure may be reduced 4% to 9% with ␤-blocker treatment. [15][16][17][18][19][20] In a recent study, we showed that ␤-blockade reduces the basal metabolic rate by 12% in obese hypertensive patients, compared with obese hypertensive patients receiving other antihypertensive agents. 21 Astrup et al 22 provided evidence for a ␤ 2 -adrenergic receptor-mediated facultative thermogenic component in skeletal muscle and a ␤ 1 -adrenergic receptor-mediated component in nonmuscle tissue.…”
Section: Potential Mechanismsmentioning
confidence: 97%
“…Therefore, beta-blockers should be avoided or used with caution in patients with hypotension and they are contraindicated in patients with significant sinus bradycardia and partial atrioventricular block [4]. Therapy with beta-blockers can also reduce exercise capacity and impair sexual function in some patients [49, 50]. Similar to beta-blockers, CCBs also exert their effects by lowering blood pressure and heart rate; therefore, nondihydropyridine CCBs are contraindicated in patients with left ventricular systolic dysfunction with or without heart failure and in patients with heart block and disorders of the sinus node [4].…”
Section: Treatment Options For Chronic Stable Anginamentioning
confidence: 99%